PENDIDIKAN ISLAM PERSPEKTIF TGKH. MUHAMMAD ZAENUDIN ABDUL MADJID AL ANFANANI - Sunardi Sunardi; M. Hamzan (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2021)
TGKH. Muhammad Zaenudin Abdul Madjid Al Anfanani has what is stated as output a qualified (student), this is evidenced by the success of his students becoming religious and social figures/leaders who take part in various fields. Be it education, politics, economy, da'wah, environment, social. almost all of the students become Tuan Guru with each of the educational institutions they lead. This can not be separated from the integration of knowledge that he initiated. This certainly cannot be separated from the education that has been obtained. The conclusion of the study states that understanding the task of humans as kholifah of Allah on earth, then Islamic education from the perspective of TGKH. Muhammad Zaenudin Abdul Madjid is understood as a process of internalizing knowledge to foster students' awareness of human duties as kholifah ( substitute/leader) on earth, as taught in Islam, by building awareness through upholding the truth, namely Islamic values ??and teachings. So that the purpose of Islamic education is to foster awareness of students about human duties as kholifah (substitute/leader) on earth, as taught in Islam, by building awareness through upholding the truth, namely the values ??and teachings of Islam.